Risk Management of Birdwatching Saporkren Tourism Destination, Raja Ampat - Siti Jahroh; Lokita Rizky Megawati; Robinsar Jogi Y Manullang; Alfa Chasanah (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
Raja Ampat is a famous tourism object for diving with hundreds of beautiful spots. However, there is a tourism spot which is specialized for birdwatching at Saporkren in Raja Ampat. Compared to the number of tourists coming for diving, those coming for birdwatching is low. This paper aims to analyze risk management of Saporkren in coping with current issues, specifically, (1) to identify the main current problem with its consequences and causes, and (2) to provide possible solutions. This study employed problem and solution trees (PASTs) analyses. The respondents interviewed include forest group leader who manages the birdwatching area, the staff members of West Papua Natural Resources Conservation Agency, the tour guide leader, the tourist, and the local government officer. This study figured out the main problem is the low number of tourists coming to Saporkren. This is due to the lack of interesting attractions, facility, quality of tour guide and security related to the issues of riots and Covid-19, leading to the root cause of lack of commitment and cooperation between management of Saporkren and its stakeholders. Based on the possible solutions, the birdwatching Saporkren can exploit the potential attractions like exotic wildlife, local cuisine festivals and competitions in Saporkren to develop and prepare the implementation of standard procedures of Covid- 19. Keywords: main problem, problem tree analysis, solution, solution tree analysis